IBU DALAM KARYA SENI GRAFIS - CINDI RAMALISA; Ariusmedi Ariusmedi (Serupa The Journal of Art Education, 2021)
This work aims to visualize the sacrifice of a mother as well as a reminder to every child that the importance of being devoted to parents, especially mothers. The methods in the creation of this artwork are: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Concept Realization, (5) completion. The result of the artwork is to visualize the portrait of the mother in the form of graphic artwork to be displayed, ten titles of the work are displayed as follows: 1) God's Deposition 2) Two Best Years 3) The Most Beautiful Anughrah 4) First Teacher 5) Sincerity 6) Responsibility 7) Hope 8) Companions 9) Way Home 10) Gifts.Keywords: Mother, Artwork, Graphics